Peran Komunitas Arthropoda Tanah dalam Upaya Pelestarian Agroforestri Berbasis Sengon dengan Tanaman Budidaya Porang (Amorphopallus muelleri Blumei) - Fujianor Maulana (Rawa Sains: Jurnal Sains STIPER Amuntai, 2015)
Land-use change forest conversion and poor land management have damaged forest ecosystem. It is automatically disturbing the components in the forest ecosystem, among other soil arthropods. Therefore, environmental friendly land management system is required. One such system is Sengon-based Agroforestry with Porang Cultivation. The objective of research is (1) to understand the structure and function of soil arthropods in the Porang and non-Porang lands; Research is conducted at KPH Saradan, Madiun Regency. Two locations are chosen, Agroforestry land with Porang cultivation and non-Porang Agroforestry land. Method of research is observational survey. Sampling technique toward Arthropod is Pitfall Trap. Result of research indicates that the diversity of soil Arthropods family in the Porang land is counted to 27 families, while in the non-Porang land, 30 families of soil Arthropods are estimated. Shannon-Wienner Diversity Index in the non-Porang land is in low category with H>1 (1.32), while the diversity index in the Porang land is in very low category with H<1 (0.83). Bray-Curtis Index, which is measuring the similarity of two compositions of land community in the Porang and non-Porang lands, is counted to 0.91, submitting to the category of not different. The community of land Arthropods in the Porang land plays some roles such as soil decomposer (57 %), litter transformer (22%), and predator (21%). The roles of litter transformer and predator have similar rate (26 %).